2015
DOI: 10.1159/000437057
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Ranibizumab and Bevacizumab on Platelet Activation Profile

Abstract: Purpose: The aim of the study was to evaluate the potential influence of ranibizumab and bevacizumab on platelet activation and aggregation, which are critical processes in the pathogenesis of arterial thromboembolic events (ATEs). Methods: For the assessment of platelet function, flow cytometry and aggregometry were employed. Platelets were isolated from healthy volunteers and exposed to ranibizumab (1 mg/ml and 150 ng/ml) and bevacizumab (2.5 mg/ml and 3 μg/ml) or their solvents for 10 and 30 min prior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In the previous experiments, we observed that activation-dependent platelet function is more impaired with aflibercept and bevacizumab compared to ranibizumab, without any impact on platelet aggregation. Moreover, FITC-labeled aflibercept and bevacizumab, as well as ranibizumab, were significantly upregulated in activated platelets [21,22]. erefore, the anti-VEGF agents might be transported into platelets and then localized in one of three major granule types: α-granules, dense granules, and lysosomes; this can be demonstrated by immunofluorescence and electron microscopy [46][47][48][49].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the previous experiments, we observed that activation-dependent platelet function is more impaired with aflibercept and bevacizumab compared to ranibizumab, without any impact on platelet aggregation. Moreover, FITC-labeled aflibercept and bevacizumab, as well as ranibizumab, were significantly upregulated in activated platelets [21,22]. erefore, the anti-VEGF agents might be transported into platelets and then localized in one of three major granule types: α-granules, dense granules, and lysosomes; this can be demonstrated by immunofluorescence and electron microscopy [46][47][48][49].…”
Section: Discussionmentioning
confidence: 95%
“…Until now, the uptake and intracellular transport of anti-VEGF agents have been investigated in retinal endothelium and retinal pigment epithelium; however, little is known about these mechanisms in platelets [6,[19][20][21]. We have previously shown that increased levels of FITC-labeled ranibizumab, aflibercept, and bevacizumab were found using fluorescenceactivated cell sorting (FACS) analysis after the activation of platelets with either thrombin receptor-activating peptide-6 (TRAP), proteinase-activated receptor 4-activating peptide (PAR-4-AP), or thrombin [21,22]. erefore, the question arises as to whether all anti-VEGF agents are taken up by platelets and which mechanisms are involved in their endocytosis by platelets (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, platelet exposure to higher bevacizumab concentrations resulted in inhibition of platelet activation. 10 Another study demonstrated different results. More precisely, platelet exposure to a mixture of bevacizumab and VEGF-A or to a mixture of aflibercept and VEGF-B or placental growth factor resulted in their activation, while ranibizumab had no effect on the platelets.…”
Section: Discussionmentioning
confidence: 98%
“…5 Several biomarkers have been evaluated to study coagulation alterations that result in hypercoagulability, and therefore, potentially increased thromboembolic risk in patients under systemic chemotherapy or under treatment with intravitreal injections of ranibizumab or bevacizumab. 611…”
Section: Introductionmentioning
confidence: 99%
“…In another study, oxaliplatin-based chemotherapy affected platelets in the liver; the number attached to liver cells positively correlated with sinusoidal-obstruction syndrome severity (221). Oxaliplatin-based damage to hepatic sinusoids can possibly attract and activate platelets (228)(229)(230). Once activated, platelets secrete growth factors such as plateletactivating factor and thromboxane A 2 , causing liver injury, vascular and sinusoidal occlusion, and collagen deposition (231,232).…”
Section: Therapy-inducedmentioning
confidence: 99%